Financial Declines, Financial Behaviors, and Relationship Satisfaction during the Recession - Jeffrey P Dew; Jing Jian Xiao (Journal of Financial Therapy, 2013)
Using nationally-representative data collected during the summer of 2009 (N = 575), this study examines how reports of financial declines are associated with financial behaviors and how financial behaviors are associated with relationship satisfaction among cohabiting and married participants. Findings suggested that financial declines were only negatively associated with sound financial management behavior if participants also experienced feelings of economic pressure. Sound financial management behavior was found to be positively associated with marital satisfaction. Finally, sound financial management behavior also moderated the association between financial declines, economic pressure, and relationship satisfaction.
Keywords: family studies; marriage and family therapy; financial therapy